The Effect of Teaching Biology Using an E-Learning Platform on Social Communication among Tenth Grade Students - Fatema Haitham Alrawahneh (Deanship of Scientific Research (DSR), the University of Jordan, 2020)
The study aims to identify the effect of teaching biology using an e-learning platform on social communication among tenth grade students. The study sample consisted of two groups that were chosen intentionally, one of them formed the experimental group, numbering (19) students, while the second formed a control group numbering (20) students. A measure of social communication skills, consisting of (20) items, was prepared to measure the effect of teaching using an e-learning platform on social communication among tenth graders studying biology. The validity and reliability of the study tools were confirmed. The results showed that there were statistically significant differences between the mean scores on the three dimensions of the social communication skills scale: communication with others, communication with the teacher, and communication with colleagues, in addition to the scale as a whole due to the teaching method and in favor of the experimental group that was taught using the platform. The study recommends generalizing the experience of using an e-learning platform and benefiting from it in developing social communication skills among tenth graders.